PENGARUH MULTIMEDIA MACROMEDIA FLASH TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK PADA MATERI POKOK PERSEGI PANJANG DAN PERSEGI KELAS VII DI MTS AL-ULUM MEDAN T.P. 2016/2017 - Zahwa Syah Putri; Fibri Rakhmawati (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to determine (1) students' mathematics learning outcomes by using macromedia flash multimedia (2) students' mathematics learning outcomes using conventional learning (3) the effect of multimedia macromedia flash on students' mathematics learning outcomes. This research is a quantitative research, with research type quasi experiment (quasi experiment). The population is all students of class VII MTs Al-Ulum Medan Lesson Year 2016/2017. The sample of this study were students of class VII-6 which amounted to 36 people as an experimental class taught using multimedia macromedia flash, and students of class VII-5 totaling 34 people as a control class taught by conventional. From the data analysis, the findings obtained are differences in the learning outcomes of students in the experimental class using macromedia flash multimedia and control classes that use conventional learning. In the study, the average value of the experimental class for pretest (initial test) was 57.92 with a standard deviation of 10.09 while for posttest (final test) was 75.97 with a standard deviation of 10.34 higher than the previous average value . In the control class the average value obtained for pretest (initial test) was 56.0 with a standard deviation of 11.13 while for the average posttest score (final test) of 69.56 with a standard deviation of 8.38 higher than the previous average value. To test the hypothesis that there is a significant influence between multimedia macromedia flash on mathematics learning outcomes learners Mts Al-Ulum Medan. Where proved that thitung> ttable is 2,848> 1,994.